Atomic level structure of Ge-Sb-S glasses: Chemical short range order and long Sb-S bonds - Pethes, I; Nazabal, Virginie; Ari, J.; Kaban, I; Darpentigny, J.; Welter, E.; Gutowski, O.; Bureau, B.; Messaddeq, Y.; Jovari, P. (Elsevier Science SA, 2019)
The structure of Ge20Sb10S70, Ge23Sb12S65 and Ge26Sb13S61 glasses was investigated by neutron diffraction (ND), X-ray diffraction (XRD), extended X-ray absorption fine structure (EXAFS) measurements at the Ge and Sb K-edges as well as Raman scattering. For each composition, large scale structural models were obtained by fitting simultaneously diffraction and EXAFS data sets in the framework of the reverse Monte Carlo (RMC) simulation technique. Ge and S atoms have 4 and 2 nearest neighbors, respectively. The structure of these glasses can be described by the chemically ordered network model: Ge-S and Sb-S bonds are always preferred. These two bond types adequately describe the structure of the stoichiometric glass while S-S bonds can also be found in the S-rich composition. Raman scattering data show the presence of Ge-Ge, Ge-Sb and Sb-Sb bonds in the S-deficient glass but only Ge-Sb bonds are needed to fit diffraction and EXAFS datasets. A significant part of the Sb-S pairs has 0.3-0.4 angstrom longer bond distance than the usually accepted covalent bond length (similar to 2.45 angstrom). From this observation it was inferred that a part of Sb atoms have more than 3 S neighbors.
Struktura skel Ge-Sb-S na atomární úrovni: chemické uspořádání na krátkou vzdálenost a dlouhé vazby Sb-S
Keywords: chalcogenide glasses; Ge-Sb-S; structure; diffraction; EXAFS; chakogenidová skla; Ge-Sb-S; struktura, difrakce; EXAFS